Widespread reticulate evolution in an adaptive radiation - DeBaun, Dylan; Rabibisoa, Nirhy; Raselimanana, Achille; Raxworthy, Christopher John; Burbrink, Frank T. (Dryad, 2023)
A fundamental assumption of evolutionary biology is that phylogeny follows
a bifurcating process. However, hybrid speciation and introgression are
becoming more widely documented in many groups. Hybrid inference studies
have been historically limited to small sets of taxa, while exploration of
the prevalence and trends of reticulation at deep time scales remains
unexplored. We study the evolutionary history of an adaptive radiation of
109 gemsnakes in Madagascar (Pseudoxyrhophiinae) to identify potential
instances of introgression. Using several network inference methods, we
find twelve reticulation events within the 22-million-year evolutionary
history of gemsnakes, producing 28% of the diversity for the group,
including one reticulation that resulted in the diversification of an 18
species radiation. These reticulations occur at nodes with high gene tree
discordance. Hybridization events occurred between north-south distributed
parentals that share similar ecologies. Younger hybrids occupy
intermediate contact zones between the parentals, showing that
post-speciation dispersal in this group has not eroded the spatial
signatures of introgression. Reticulations accumulated consistently over
time, despite drops in overall speciation rates during the Pleistocene.
This suggests that while bifurcating speciation may decline as the result
of species accumulation and environmental change, speciation by
hybridization may be more robust to these processes.
Keywords: adaptive radiation; Hybridization; Introgression; Macroevolution; networks; FOS: Biological sciences